2017
DOI: 10.1016/j.pmedr.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

“Knowledge, recommendation, and beliefs of e-cigarettes among physicians involved in tobacco cessation: A qualitative study”

Abstract: Physicians are rated the most trustworthy source of information for smokers and thus play an increasing role in disseminating information on e-cigarettes to patients. Therefore, it is important to understand what is currently being communicated about e-cigarettes between physicians and patients. This study explored the knowledge, beliefs, communication, and recommendation of e-cigarettes among physicians of various specialties. Semi-structured interviews were conducted in early 2016 with 35 physicians across f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
55
0
17

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(87 citation statements)
references
References 23 publications
15
55
0
17
Order By: Relevance
“…Our findings also showed that just over half of the reported discussions about NVPs were initiated by the smokers themselves, and not by the HP, which may indicate that HPs do not feel entirely comfortable or confident bringing up the topic. This has also been found in other studies, where reasons for not advising about NVPs have included the HP's perceived uncertainty about the safety and efficacy of NVPs , negative beliefs , lack of knowledge , and lack of confidence in their own capacity to counsel smokers about NVPs . These cited studies, however, have mainly been conducted in the United States using convenience samples, with limited data on common practices in other countries.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Our findings also showed that just over half of the reported discussions about NVPs were initiated by the smokers themselves, and not by the HP, which may indicate that HPs do not feel entirely comfortable or confident bringing up the topic. This has also been found in other studies, where reasons for not advising about NVPs have included the HP's perceived uncertainty about the safety and efficacy of NVPs , negative beliefs , lack of knowledge , and lack of confidence in their own capacity to counsel smokers about NVPs . These cited studies, however, have mainly been conducted in the United States using convenience samples, with limited data on common practices in other countries.…”
Section: Discussionmentioning
confidence: 66%
“…Our findings showed that, overall, fewer than 10% of smokers reported having a discussion about NVPs with an HP in the last year. Moreover, a number of studies have shown that HPs are divided about recommending NVPs for smoking cessation . The results herein have shown that HPs rarely recommended NVPs to smokers (only 2% of smokers were encouraged to use an NVP, which was approximately a third among those who had a conversation about the topic).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…26 Physicians have rated the most trusted sources of information for smokers; thus, they play the main role in disseminating information to the general population. 27 Therefore, this study was conducted to compare the knowledge and beliefs about electronic cigarettes between the health care providers either physicians or nurses who deliver education and guidance about electronic cigarettes and the general population who use it in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…Data were analysed using framework analysis, which has been shown to be applicable for studying influences on the uptake of behavioural support and vaping , including the role health professionals may play in such decisions . A sample of transcripts were carefully examined by the lead author in order to produce initial coding/thematic frames for the smoker and SSS interviews respectively.…”
Section: Methodsmentioning
confidence: 99%